Unraveling of Chlorella-associated bacterial load, diversity, and their imputed functions at high- and low-yield conditions through metagenome sequencing - Madhubalaji, Chegu Krishnamurthi (Journal of phycology, 2022)
© 2021 Phycological Society of America.